Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Perusahaan Daerah Air Minum Tirta Jam Gadang Kota Bukittinggi Sumatera Barat - Sabri; Heliyani; Aznam, Muhammad Fakhri; Febrianti, Eka; Asnah (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Data were collected through the distribution of questionnaires with a Likert scale model and then tested for validity and reliability of the questionnaire. The data analysis technique used is the Binary Logistic method. The results of this study are a). Physical evidence, There is a Positive and Significant Influence on Customer Satisfaction of Clean Water at the Regional Public Drinking Water Company Tirta Jam Gadang, Bukittinggi City. b). Empathy, There is a Positive and Significant Influence on Customer Satisfaction of Clean Water at the Regional Public Drinking Water Company Tirta Jam Gadang, Bukittinggi City. c). Responsiveness, There is a Positive and Significant Influence on Customer Satisfaction of Clean Water at the Regional Public Drinking Water Company Tirta Jam Gadang, Bukittinggi City. d). Reliability, There is a Positive and Significant Influence on Customer Satisfaction of Clean Water at the Regional Public Drinking Water Company Tirta Jam Gadang, Bukittinggi City. e). Assurance, There is a Positive and Significant Influence on Customer Satisfaction of Clean Water at the Regional Public Drinking Water Company Tirta Jam Gadang, Bukittinggi City. The most dominant variable influencing Clean Water Customer Satisfaction at the Tirta Jam Gadang Regional Drinking Water Company in Bukittinggi City is Empathy.